Examining dose-response of an outdoor walk group program in the Getting Older Adults Outdoors (GO-OUT) trial. - Tai-Te Su; Ruth Barclay; Rahim Moineddin; Nancy M Salbach (PLoS ONE)
Objective The Getting Older Adults Outdoors (GO-OUT) randomized trial showed that a 10-week outdoor walk group (OWG) program was not superior to 10 weekly phone reminders in increasing physical and mental health; however, OWG attendance varied. This study examined whether dose-response relationships existed between OWG attendance and improvement in physical and mental health among older adults with mobility limitations. Methods We analyzed data from 76 OWG participants with pre- and post-intervention scores on at least one of seven measures of health outcomes (walking endurance, comfortable and fast walking speed, balance, lower extremity strength, walking self-efficacy, and emotional well-being). Participants were classified as attending 0-9, 10-15, and 16-20 OWG sessions based on attendance tertiles. We adjusted for participant sex and study site in regression analyses. Results Among the 76 participants, mean age was 74.9 ± 6.6 years and 72% were female. Compared to those attending 0-9 OWG sessions, participants attending 16-20 sessions exhibited a 56.3-meter greater improvement in walking endurance (95% CI: 17.3, 95.4, p = 0.005); 0.15-meter/second greater improvement in comfortable walking speed (95% CI: 0.01, 0.29, p = 0.034); and 0.18-meter/second greater improvement in fast walking speed (95% CI: 0.03, 0.34, p = 0.020). Higher attendance was associated with greater odds of improvement in comfortable walking speed (OR = 7.1; 95% CI: 1.1, 57.8, p = 0.047) and fast walking speed (OR = 10.1, 95% CI: 1.8, 72.0, p = 0.014). No significant dose-response relationships for the remaining outcomes were observed. Conclusions Higher attendance in a park-based, supervised, task-oriented and progressive OWG program is associated with greater improvement in walking endurance and walking speed among older adults with mobility limitations. Attendance likely impacted walking capacity and not balance, lower extremity strength, walking self-efficacy or emotional well-being due to task-specificity of training. This study highlights the importance of attendance when designing and implementing OWG programs to enhance walking endurance and speed among older adults.